Selection and Characterization of Single-Domain Antibodies for Detection of Lassa Nucleoprotein - Anderson, George P. (Antibodies (Basel), 2020)
Lassa virus is the etiologic agent of Lassa fever, an acute and often fatal illness endemic to West Africa. It is important to develop new reagents applicable either for the specific diagnosis or as improved therapeutics for the treatment of Lassa fever. Here, we describe the development and initial testing of llama-derived single-domain antibodies that are specific for the Lassa virus nucleoprotein. Four sequence families based on complementarity-determining region (CDR) homology were identified by phage-based enzyme-linked immunosorbent assays, however, the highest affinity clones all belonged to the same sequence family which possess a second disulfide bond between Framework 2 and CDR3. The affinity and thermal stability were evaluated for each clone. A MagPlex-based homogeneous sandwich immunoassay for Lassa virus-like particles was also demonstrated to show their potential for further development as diagnostic reagents.